(untitled) (Revista cientifica In Vestigium Ire, 2015)
The generation of knowledge across the scientific investigation meets demanded to giving response to the pressures and needs of the environment, concretely from the priorities of the productive organizations and of the market. Nowadays, the knowledge authorized already does not generate only in the University, which has deep implications in his hegemony and in the form in which the company itself sees to this institution. In the company of the knowledge, the companies and other private entities seem to worry for the creation of the knowledge, so much or more than the own State. The pressure for the innovation crosses the whole social fabric and knowledge is not understood externally of the generation again, with aptitude to be used and assimilated collectively. There, the tension between knowledge and interest takes a particular embossment, since the altruistic ends and the mechanisms that accompany the processes of production of knowledge in the academy are seen displaced and / or transformed in a scene of new economic priorities. (Habermas, 1982) It is undeniable that in the area of the administrative and countable sciences the nature of such knowledge claims a very deep link with the world organizacional. This way, the applied investigation becomes more relevant and reliable to know the managerial world, when it is supported in conceptual frames and theoretical robust structures, which are own of the basic investigation and which allow to deliver explanatory and comprehensive sense to the empirical events; which implies that not only the application is valid for the investigation in our disciplines. (Mora-Osejo and Fals-hut, 2004) Hereby, the link between University, on one hand, and managerial and bought environment, for other one, needs to be permanently rethought and reconstructed. We must understand that the comprehension, intervention and transformation of our reality claims a process disciplined and compromised with the delivery of tangible results, which reverberate in suggestions and strategies of action for the medium and long term. Though the diffusion of the results of investigation first needs of the expert lens of the academicians to guarantee the scientific character of the findings and the responsible autorregulación, it is not less true than the investigation the limited space of the cloisters must come out, impressing the actors with capacity of political and economic decision and to the public opinion. For these reasons, between others, from this scene, across the Magazine IN VESTIGIUM IRE, we invite the academicians of the administrative and countable sciences - as well as as of other social sciences-, in order that together with other generating factors of knowledge and development there appear debates and reflections that allow to increase our comprehension of the reality organizacional of the region, the country and the included world. We trust that our readers will find valuable the works that are revealed in the present volume, recognizing that our collaborators continue reaching to the comprehension of the dynamics organizacional and socioeconomic, in a complex environment and challenger as the one that faces today the University worldwide.